Aktivisme Warga dan Negara dalam Kerusakan Lingkungan di Lebak Banten - Sinta Agustina, Dewi; Ma'asan Mayrudin, Yeby (Indonesian Democracy Research Center, 2023)
Environmental damage caused by the negative impact of industrial activities in the Bayah District area which causes public complaints about health. This triggers the emergence of community activism gathered in JMPB with its role which always strives for environmental sustainability and demands industry accountability by reporting directly on forms of pollution to the government so that the government pays more attention to the impact of industry on the environment. The purpose of this study is to find out how the emergence of social movements in Bayah, JMPB’s efforts in reducing environmental damage, and the role of the government in supervising and evaluating industry in Bayah. This research uses a qualitative method with a case study approach. The results showed that the emergence of social movements in Bayah was caused by the presence of PT Cemindo Gemilang which produces cement and has an impact on the environment and public health. The role of JMPB as an indirect actor is conducting protests, environmental socialization, parallel training, reforestation, and reposting forms of pollution to the authorities. Meanwhile, the role of DLH Lebak Regency as a direct actor who has an important role in environmental supervision and can provide sanctions to the industry in accordance with indications of environmental damage that occurs.